ENHANCING LISTENING MOTIVATION OF A1-LEVEL ENGLISH LEARNERS THROUGH THE 4C MODEL - Abatov A. K. (Modern American Journals, 2026)
This article examines the effectiveness of the 4C model (Creativity, Critical Thinking, Communication, and Collaboration) in enhancing listening comprehension motivation among A1-level English language learners. In the context of modern foreign language education, the development of listening skills at the beginner level plays a crucial role in shaping learners’ overall communicative competence. The study emphasizes that A1 learners often face psychological barriers, limited vocabulary, and low confidence, which can negatively affect their engagement in listening activities. Integrating the 4C model into listening instruction provides a learner-centered and supportive learning environment that fosters active participation and intrinsic motivation.
Keywords: 4C model, A1 level learners, listening comprehension, learning motivation, English language teaching, collaborative learning.